(untitled) (Journal of Management & Business, 2023)
Investors and primary users of general-purpose financial information need sustainability actions that have a financial impact to be contained in published and audited annual reports. The objective of this research is to analyze whether it is possible, based on an adequately designed accounting system, to have information that links financial performance with the sustainability strategies of an organization, providing stakeholders with information that summarized all entity actions at a given time. To this end, the disclosures on actions that respond to sustainability strategies included in reports issued by companies in Argentina that adopt generally accepted guidelines on the matter were analyzed. This information was related to investments, liabilities, expenses, and income disclosed in Financial Statements, considering the same period. As differences were detected, it is noted that corrective measures are necessary. It is crucial to open a debate on the mandatory accounting recognition of those transactions, actions, omissions, or other issues related to an entity sustainable performance, which may put at risk the organization going concern. Based on the analysis carried out in the companies selected, a link that reveals coincidence between what is stated in both Sustainability Reports and Financial Statements for the same period cannot be determined. Although in relation to sustainable performance there are data that cannot be measured objectively, and consequently are not recognized in the financial statements, lack of harmony between the two reports analyzed for each company suggests in first place that different work teams participated in the information issuance process. Besides, information needs were prioritized for different users, not providing exhaustive data. The final recommendations focus mainly on legitimizing leadership in the information issuance process to avoid inconsistencies, differences, and omissions, on training the main actors in the information issuance processes, and on awakening the sensitivity of economic science professionals. that participate actively advising and helping organizations to raise the quality of their disclosures.